Effect of Concentration of Ti Doping on Optical Properties of Zn1-xTixO (where x=0.0, 0.1, 0.3, 0.5, 0.7 and 0.9) Thin Films Deposited by Spray Pyrolysis - Chand, Sansar; Reena Rani; Yadav, Kamlesh (Asian Journal of Engineering and Applied Technology, 2016)
Ti doped Zn1-xTixO (where x=0.0, 0.1, 0.3, 0.5, 0.7 and 0.9) thin films have been deposited on Indium Tin Oxide (ITO) coated glass substrate at 4500 C. The effects of Ti doping concentration on the optical properties in ZnO films have been studied. The deposited films are characterized by Field Emission Scanning Electron Microscope (FESEM), Energy- Dispersive X-ray Spectroscopy (EDS), UV-Visible Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR) techniques. The FESEM studies reveal that the particle size decreases from 16 nm to 9 nm with increase in Ti concentration from x=0.0 to 0.9. Analysis of UV- visible spectra shows that the optical direct band gap increases from 3.92 eV up to 4.68 eV with increase in Ti doping concentration x=0.0 to 0.9. The FTIR spectra of the films shows Zn-O absorption band in between (450-487) cm-1. The peaks also appear in between (3000-4000) cm-1, (2885 2100) cm-1 and at 530 cm-1 due to O-H, N-H and Ti-O bond stretching respectively. EDS result shows that Zn, O and Ti elements are present as per their stoichiometric ratio in all the prepared samples.